Empowering Digital Language Literacy in Writing Instructions: Lecturers’ and Students’ Voices - Masriatus Sholikhah; Candradewi Wahyu Anggraeni (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
In facing the metaverse era, technology in language instruction plays an essential role in elevating students’ digital literacy. It leads teachers to integrate digital tools utilization in the instructional context to accommodate the students’ need for productive and meaningful learning. Following this issue, this research explores teachers’ and students’ voices regarding the empowerment of Digital Language Literacy in writing instructions. The research method used in this study is a case study. Researchers administered interviews and questionnaires as data collection instruments in obtaining the data. The open-ended interview was carried out with the lecturers of writing courses. Besides, the close-ended questionnaire was also administered to the students of writing courses. The participants of this current study were 3 lecturers and 40 students from two universities in Indonesia. To uphold the theoretical lens of Digital Language Literacy, this research uses and adapts the theory of Eshat (2004) and Porat, Blau & Barack (2018) as the underlying framework. The results showed the three aspects of lecturers’ and students’ perspectives in which they cover Digital Language Literacy implementation, Digital Language Literacy challenges and opportunities, and the ways to empower Digital Language Literacy in the writing instructions. As a result, the research findings contribute to improving digital language literacy implementation, specifically in teaching writing in EFL Higher Education context.